Analisis Kemampuan Literasi Digital Pada Siswa Kelas XI MIPA SMA Negeri 1 Singaparna: (Analysis of Digital Literacy Skills in XI MIPA Students of SMA Negeri 1 Singaparna) - Hendrawan, Al Maidah; Aufa, Elia Amanda; Fauziah, Lutfi; Putri Lestari, Dinda; Khodijah, Piljah (BIODIK, 2024)
Digital literacy skills are essential in the world of education and must be possessed by all levels of society without exception. Digital literacy plays an important role in determining the success of students' learning in today's digital era. This study aims to determine the level of digital literacy skills of class XI MIPA students of SMAN 1 Singaparna. The research method used is quantitative descriptive. The data collection technique used in this study is a survey technique. The instrument used is a questionnaire containing statements related to digital literacy with a linkert scale. Based on the analysis of the results of the study related to students' digital literacy skills that have been carried out, it can be concluded that students' digital literacy in using social media to communicate, obtain information, entertainment, shopping and find alternative learning sources is good. However, students have not been able to process the information obtained so that the level of students' digital literacy needs to be improved again. Abstrak. Kemampuan literasi digital sangat diperlukan dalam dunia pendidikan dan harus dimiliki oleh seluruh lapisan masyarakat tanpa terkecuali. Literasi digital berperan penting dalam menentukan keberhasilan belajar peserta didik di era digital saat ini. Penelitian ini bertujuan untuk mengetahui tingkat kemampuan literasi digital siswa kelas XI MIPA SMAN 1 Singaparna. Metode penelitian yang digunakan adalah kuantitatif deskriptif. Teknik pengumpulan data yang digunakan pada penelitian ini adalah teknik survei. Instrumen yang digunakan berupa kuisioner yang berisi pernyataan-pernyataan terkait literasi digital dengan skala linkert. Berdasarkan analisis hasil penelitian terkait kemampuan literasi digital siswa yang telah dilakukan, maka dapat disimpulkan bahwa literasi digital siswa dalam menggunakan media sosial untuk berkomunikasi, memperoleh informasi, hiburan, berbelanja dan mencari alternatif sumber belajar sudah baik. Namun, siswa belum bisa mengolah informasi yang didapat sehingga tingkat literasi digital siswa peru ditingkatkan kembali.